2014
DOI: 10.1051/0004-6361/201423490
|View full text |Cite
|
Sign up to set email alerts
|

B fields in OB stars (BOB): The discovery of a magnetic field in a multiple system in the Trifid nebula, one of the youngest star forming regions

Abstract: Aims. Recent magnetic field surveys in O-and B-type stars revealed that about 10% of the core-hydrogen-burning massive stars host large-scale magnetic fields. The physical origin of these fields is highly debated. To identify and model the physical processes responsible for the generation of magnetic fields in massive stars, it is important to establish whether magnetic massive stars are found in very young star-forming regions or whether they are formed in close interacting binary systems. Methods. In the fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Evolutionary tracks of Brott et al (2011) for initial rotational velocity of ∼300 km s −1 are shown (full lines), labelled by initial stellar mass. The magnetic star in the Trifid nebula and HD 345439 (Hubrig et al 2014(Hubrig et al , 2015b are not included here because of difficulties in establishing their properties. (Lotkin & Matkin 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary tracks of Brott et al (2011) for initial rotational velocity of ∼300 km s −1 are shown (full lines), labelled by initial stellar mass. The magnetic star in the Trifid nebula and HD 345439 (Hubrig et al 2014(Hubrig et al , 2015b are not included here because of difficulties in establishing their properties. (Lotkin & Matkin 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Hubrig et al (2014a) reported the detection of a rather strong magnetic field on the basis of FORS2 and HARPSpol data. Figure 7 illustrates the clear detection of the magnetic field at the ∼9σ level, already reported by Hubrig et al (2014a) 6 .…”
Section: New Detections: Hd 54879 Hd 164492c and Cpd −57 3509mentioning
confidence: 99%
“…Hubrig et al (2014a) reported the detection of a rather strong magnetic field on the basis of FORS2 and HARPSpol data. Figure 7 illustrates the clear detection of the magnetic field at the ∼9σ level, already reported by Hubrig et al (2014a) 6 . The high-resolution HARPSpol observations and further high-resolution UVES spectra revealed that HD 164492C is in fact a multiple system, composed of at least two stars.…”
Section: New Detections: Hd 54879 Hd 164492c and Cpd −57 3509mentioning
confidence: 99%
“…This setting led to a resolving power of approximately 1700 and a wavelength coverage from 3250-6215 Å. Eight consecutive exposures of 600 s were carried out with a total exposure time of 4800 s. More details on the instrument settings and exposure sequence are provided by Hubrig et al (2014a;see also Fossati et al 2015b).…”
Section: Observationsmentioning
confidence: 99%
“…The HARPSpol data were independently reduced and analysed using different techniques by the Bonn and Potsdam groups, as described in previous BOB works (Hubrig et al 2014a;Przybilla et al 2016).…”
Section: The Strong Surface Magnetic Field Of Cpd −62 • 2124mentioning
confidence: 99%